Three-dimensional numerical and experimental investigation of an industrial-sized SOFC fueled by diesel reformat – Part II: Detailed reforming chemistry and carbon deposition analysis. (14th September 2015) - Schluckner, C.; Subotić, V.; Lawlor, V.; Hochenauer, C.
Abstract: As an important energy source, liquid diesel can be reformed in order to be used in high temperature solid oxide fuel cells (SOFCs) cleanly and efficiently. However, a big challenge of using carbon containing fuels, such as diesel reformat, is carbon deposition on the porous Ni/YSZ-anode structure caused by internal reforming reactions. In this work a planar industrial-sized 100 × 100 mm 2 anode supported SOFC fueled with synthetic diesel reformat was numerically and experimentally investigated, in order to predict carbon depositions in the porous anode substrate. Gas phase as well as detailed wall-surface reactions were scrutinized in order to evaluate reforming mechanisms available in literature. Implementation and simulation was done by one single 3D CFD simulation tool, since such a comparison is missing in the scientific community. It was shown that global reforming mechanisms are capable of correctly predicting the occurring gas phase reactions, but only provide indicators for the thermodynamic equilibria of considered carbon formation pathways. Detailed information about surface adsorbed carbon can only be determined by a heterogeneous reaction mechanism. Elementary carbon was shown to be permanently adsorbed onto the catalytic active sites in the anode by the conducted steady state simulations. The investigations showed that the inlet region of the porous anodic structure is especially susceptible to coking. Simulation results were validated with in-house experimentally determined data. High cell current densities were reached during the single cell experiments, which determine good electrical contacting as well as electrochemical performance and therefore represent reliable validation data. Highlights: 3D-CFD SOFC model fueled with reformed diesel for carbon deposition simulations. In-house polarization curves and anode outlet gas composition data for validation. Analysis of homogeneous and detailed heterogeneous reforming reaction mechanisms. Weaknesses of homogeneous carbon characterization methods were highlighted. Major surface adsorbed species, including elementary carbon, were identified.